Hearing loss qualitative assessment among work from home earphone users / Jotham Ngu Ong Hu - Jotham Ngu , Ong Hu (2021)
Earphones have become a common and trendy hearing device among people in the world. The outbreak of Covid-19 pandemic has caused many workers in Malaysia to work from home. Working from home may prolong the usage of earphones and potentially cause hearing loss among workers and appear as an occupational health hazard. Thus, this research has been carried out to examine the effect of earphones towards hearing loss among work from home workers and investigate the reason and the cause of the hearing loss experienced. A hearing loss qualitative assessment has been generated and 20 respondents participated in the assessment. The qualitative assessment comprises interview questions and 3 tests namely the whispering test, the speech in noise test and the single-sided ear test. The interview analyzes the cause of hearing loss while the tests examine the ear health and detect hearing loss. As a result, the unhealthy respondents have the common characteristics, in which they are all using earphones for more than 5 hours per working day and having their earphone volume more than 65%. Hence, if the workers do not practice good earphones using habit, prolonged earphone usage during work from home possesses risks in ear health. If companies and their workers do not have proper awareness on earphones usage during the work from home period, it will eventually emerge as an occupational hearing health issue in the future.